Effects of PBAT on Soil Water and Salt in Maize Root Zone and Maize Yield in Saline-alkali Land - YANG Zhaoyu; WANG Jing; LÜ Wen; SUN Haojie; REN Hongwu; MA Weiwei; HOU Jiana (Shuitu Baochi Xuebao)
[Objective] In order to reduce soil pollution caused by plastic film, the application effect of using PBAT fully biodegradable plastic film instead of ordinary PE plastic film combined with drip irrigation to grow maize in mild secondary salinized soil was investigated. [Methods] Comparative tests were conducted on four mulching treatments, including PBAT biodegradable film (black and white) mulching, ordinary black film mulching and open-field cultivated maize without mulching, under three irrigation conditions (2 600, 3 300 and 4 200 m3/hm2) from April to September 2023 in Xinghuocun Experimental Station, Huinong District, Ningxia, and there were 12 treatments in total. The degradability of degradable film and its effect on soil water and salt transport and maize growth were studied. [Results] The water content in the 0-20 cm soil layer under black and white fully biodegradable mulch film was 18.87% and 18.34% higher than that under ordinary PE film, respectively, and 1.16% and 0.72% higher than that without mulching, respectively, and the soil salt content under black and white PBAT fully biodegradable film mulching and ordinary PE film mulching was reduced by 15.01%~23.10% compared with that without mulching (p<0.05). Compared with the non-mulching conditions with 2 600 and 3 300 m3/hm2 irrigation, the yield under black fully biodegradable film mulching increased by 11.88%~16.65%, but the difference was not significant under the irrigation condition of 4 200 m3/hm2. Compared with the yield of 2 600 m3/hm2 irrigation without mulching, the yield of white fully biodegradable film mulching increased by 13.42% under irrigation conditions, but there was no significant difference under 3 300 and 4 200 m3/hm2 irrigation conditions. The water-use efficiency of black and white PBAT fully biodegradable film mulching was increased by 23.31% and 13.50% respectively compared with ordinary PE film mulching. Compared with no-mulching, it increased by 37.63% and 26.69% respectively. [Conclusion] The study suggests that it is feasible to replace ordinary mulch film with degradable mulch film in drip irrigation agricultural production in saline-alkali lands in the irrigation areas along the Yellow River.